2013
DOI: 10.5194/nhess-13-197-2013
|View full text |Cite
|
Sign up to set email alerts
|

Burst increases of precipitating electrons recorded by the DEMETER satellite before strong earthquakes

Abstract: Abstract. This case study developed a method for data processing over six years, from 2004 to 2010, of 70 keV-2.3 MeV electrons recorded by the DEMETER (Detection of Electro-Magnetic Emissions Transmitted from Earthquake Regions) satellite. Short time increases in electron counting rates, having 99 % probabilities of not being Poisson fluctuations, were statistically selected using geomagnetic invariant space and called electron bursts. Temporal series were analysed confirming the seasonal variations in low en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 28 publications
1
24
0
2
Order By: Relevance
“…A criterion to select electron bursts has been applied on high energy electron flux data at 70 keV-2.34 MeV recorded by IDP on DEMETER (Zhang et al, 2013). The calculated time differences between CRs by IDP and EQs were longer than those of previously published works, and increases in energetic electron fluxes were observed a few days before EQs (Anagnostopoulos et al, 2010), accompanied by broadband kHz emissions (Anagnostopoulos et al, 2012;Zhang et al, 2012) and compared to the VLF transmitter contributions (Sidiropoulos et al, 2011;Sauvad et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A criterion to select electron bursts has been applied on high energy electron flux data at 70 keV-2.34 MeV recorded by IDP on DEMETER (Zhang et al, 2013). The calculated time differences between CRs by IDP and EQs were longer than those of previously published works, and increases in energetic electron fluxes were observed a few days before EQs (Anagnostopoulos et al, 2010), accompanied by broadband kHz emissions (Anagnostopoulos et al, 2012;Zhang et al, 2012) and compared to the VLF transmitter contributions (Sidiropoulos et al, 2011;Sauvad et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[56]), but also changes of high energy e flux is reported to be related to seismicity (e.g. [57,58] among others).…”
Section: Energetic Electrons and Uv Fluxmentioning
confidence: 98%
“…Except for the ionospheric data from the ground-based ionosondes and GPS receivers, some other satellite data (such as FORMOSAT3/COSMIC and DEMETER) were also utilized to study abnormal variations before earthquakes (Zhang et al, , 2010b(Zhang et al, , 2013Liu et al, , 2011bSarkar et al, 2007;Zeren et al, 2010Zeren et al, , 2012. COSMIC data further reveal that the NmF2 significantly decreases by approximately 40%, and the hmF2 drops about 50-80 km when the GPS TEC anomalously reduces .…”
Section: M79 Wenchuan Earthquakementioning
confidence: 99%
“…Zhang et al (2013) statistically analyzed the ULF electric field observed by the DEMETER satellite for 27 earthquakes in Indonesia and Chile. All of the results showed that perturbations varied from 1.5 to 16 mV/m in the upper ionosphere, and the perturbations were mainly located just over the epicenter area.…”
Section: Statistical Studiesmentioning
confidence: 99%